MHD effects on non-Newtonian power-law fluid past a continuously moving porous flat plate with heat flux and viscous dissipation - Kishan, Naikoti; Shashidar Reddy Borra (Zielona Góra: Uniwersytet Zielonogórski)
The problem of a magneto-hydro dynamic flow and heat transfer to a non-Newtonian power-law fluid flow past a continuously moving flat porous plate in the presence of sucion/injection with heat flux by taking into consideration the viscous dissipation is analysed. The non-linear partial differential equations governing the flow and heat transfer are transformed into non-linear ordinary differential equations using appropriate transformations and then solved numerically by an implicit finite difference scheme.
Keywords: magnetic field effects; non-Newtonian fluid; power-law index; viscous dissipation and suction/injection